A RARE CASE OF MULTIPLE ENDOCRINE NEOPLASIA 1 - L, Michelle Angeli; K, Soo Rah; M, Naranjo (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Multiple endocrine neoplasia type 1 (MEN-1) is a rare condition with an incidence of 1 in 30,000. It is commonly familial but sporadic forms may occur rarely. The syndrome is diagnosed by the presence of overproduction of hormones that involve either the parathyroid, pituitary and gastroenteropancreatic (GEP) tract. The parathyroid gland is the main endocrine organ that is involved in approximately 90% of patients with insulinoma accounting for only 10%. CASE We report a case of a 59-year-old male who presented with a five-month history of recurrent hypoglycemia and weight gain. The patient presented with Whipple’s triad and underwent a 72-hour fasting protocol which revealed high insulin and C-peptide levels. Computed tomography (CT) scan of the abdomen revealed a mass in the tail of the pancreas. Further work-up revealed increased intact parathyroid hormone with normal calcium level and normal pituitary gland. Patient underwent distal pancreatectomy and histopathology confirmed insulinoma. Postoperatively, there was resolution of hypoglycemia. As for the asymptomatic hyperparathyroidism, the patient will undergo yearly screening for signs of hypercalcemia. CONCUSION Hypoglycemia which is commonly encountered in the daily practice of physicians may be easily managed but beyond its simplicity it could reveal a rare syndrome commonly missed. It is important that when we are presented with a single endocrine problem, we should work up for a larger entity as missed diagnosis can have serious clinical implications.